Simultaneous enhancement of excitation and postburst inhibition at the end of focal seizures. Issue 6 (9th July 2014) - Boido, Davide; Gnatkovsky, Vadym; Uva, Laura; Francione, Stefano; de Curtis, Marco
<x xml:space="preserve">Abstract</x> Objective Comprehension of the events that lead to seizure termination contributes to the development of strategies to confine propagation of ictal discharges. It is commonly assumed that the inhibitory control fails during seizures and recovers after the end of the ictal event. We examine the possibility that a progressive increase of inhibition that counters an increase in the strength of excitation contributes to terminating a focal seizure. Methods We analyzed seizures acutely induced by pharmacological manipulations (bicuculline and 4‐aminopyridine) in the entorhinal cortex and in the hippocampus of the in vitro isolated guinea pig brain. Results As seizures ended, extracellular and intracellular recordings showed periodic bursting that progressively decreased in frequency. During the late bursting phase, the duration, number, and rate of occurrence of spikes within single bursts remained constant, whereas cumulative spike amplitude (index of excitation during a burst) and interburst interval (index of inhibition between bursts) progressively increased. The increment of average/cumulative burst excitation and interburst interval toward seizure end was confirmed in human focal seizures recorded with intracerebral electrodes in patients with drug‐resistant partial epilepsies. A postburst refractory period of circa 2 seconds that increases with time toward the end of the seizure was confirmed in the experimental model by probing interburst epochs in the CA1 region with local dentate gyrus stimulation just suprathreshold for burst generation. Interpretation Our findings support the concept that focal seizures are terminated by the simultaneous and opposing enhancement of excitation (burst activity) in addition to postburst inhibition. We hypothesize that a seizure stops when postburst inhibition becomes large enough to prevent reactivation of excitation. Ann Neurol 2014;76:826–836